Customer Relationship Management, Brand Equity, dan Kualitas Produk Pengaruhnya Terhadap Loyalitas Konsumen pada Cafe Teras Rumah Surabaya Selatan di Masa Pandemi Covid – 19 - Suraya, Reza Amalia (Universitas 17 Agustus 1945 Surabaya, 2025)
This study used quantitative research with a sample of 100 respondents from the Surabaya City community who had visited the Teras Rumah cafe in South Surabaya. The data obtained is calculatedusing statistical methods with the help of the Statistical Program For Social Science (SPSS) data processing application. The results of this study indicate that Customer Relationship Management, Brand Equity, and Product Quality have a strong influence on Consumer Loyalty at the Teras Rumah Surabaya Selatan cafe. From the results of this study, it is expected that the Teras Rumah Surabaya Selatan cafe will further improve aspects of customer relations, brand equity and product quality because these three things have a strong influence on consumer loyalty. With the improvement and improvement of these three aspects, it is expected that consumers will be more loyal to the Teras Rumah Surabaya Selatan cafe which will make the business survive in the fierce competition.